REVIEW OF CRIMINAL LAW ON LAW NUMBER 22 OF 2009 ARTICLE 24 JO ARTICLE 273 CONCERNING TRAFFIC AND ROAD TRANSPORTATION FROM THE ASPECT OF HUMAN RIGHTS - Pauzi, (Proceeding International Conference on Social Sciences, 2026)
As mandated by the 1945 Constitution of the Republic of Indonesia, traffic and road transportation have a strategic role in supporting national development and integration in an effort to advance public welfare. As part of the national transportation system, traffic and road transportation must be developed their potential and role to realize security, welfare, traffic order and road transportation in order to support the national transportation system. The fact that accidents on the highway often occur is not only due to natural factors or the fault of the rider, but also due to the large number of damaged roads, such as potholes, cracks and uneven road surfaces. In many cases, motorists die from avoiding potholes, resulting in loss of life and property. As road operators, the government must be held criminally accountable for their inability to repair roads. This paper examines Law Number 22 of 2009 concerning Road Traffic and Transportation regulates law enforcement against road accidents caused by damaged roads. This law establishes criminal sanctions for road operators who do not repair damaged roads quickly. Thus, the perpetrator or the road operator can be held responsible in accordance with the law. However, those hopes are still limited to "discourse in the law" and questions about accidents caused by damaged roads, in which motorists are still the main suspects and continue to be. If we judge from the aspect of human rights, then everyone has the right to get legal certainty in the form of safety guarantees in traffic. This study shows that based on article 273 of Law Number 22 of 2009 concerning Road Traffic and Transportation, material criminal acts committed by road operators are considered impure passive criminal acts in the case of traffic accidents that have an impact on road damage. Because the formulation of Law Number 22 of 1999 concerning Road Traffic and Transportation article 240 letter b provides legal protection for motorists who have an accident due to road damage, people who are victims of road traffic accidents can file a lawsuit against the party that caused the loss. In addition, in Law Number 22 of 1999 concerning Road Traffic and Transportation, the criminal liability of road operators to the victims.